Vegetation fire activity and the Potential Fire Index (PFIv2) performance in the last two decades (2001–2016) - Silva, Alex S.; Justino, Flavio; Setzer, Alberto W.; Avila‐Diaz, Alvaro (International journal of climatology, 2021)
Fire incidence has been linked to multiple factors such as climate conditions, population density, agriculture, and lightning. Recently, fire frequency and severity have induced health problems and contributed to increase atmospheric greenhouse gases. Based on atmospheric susceptibility to fire, this study evaluates the use of a Potential Fire Index (PFIv2) to identify regions prone to fire development, as demonstrated by the satellite detected‐fire in the 2001–2016 interval. It is demonstrated that PFIv2 delivers an efficiency by up to 80% in matching the observed fires from Terra/MODIS satellite. The PFIv2 is also able to reproduce more accurately areas with fire activity with respect to its previous version, the PFI. This better performance is linked to the implementation of parameterization of water pressure deficit and atmospheric stability in the lower troposphere, and a new term to represent the effect of surface temperatures, particularly in mid‐latitudes and extra‐Tropics. To evaluate the performance of the PFIv2 in more details, its comparison to MODIS burned areas demonstrated correlations values higher than 0.6 over the most susceptible regions such as Africa and South America, slightly lower correlation is found where fire does not primary follows the climate annual cycle, and is dominated by high frequency events. These findings indicate that the PFIv2 can be an important tool for decision makers in predicting the potential for vegetation fires development and fire danger. Based on atmospheric susceptibility to fire, we evaluate the use of a Potential Fire Index (PFIv2) to identify regions prone to fire development, as demonstrated by the satellite detected‐fire. This figure shows that in northern Australia, southern Asia, Africa, and South America experience a dominant season. In Africa, two regions are identified with maxima amplitude, which are related with the annual migration of the Intertropical Convergence Zone and associated dry season. Larger amplitude is also noted in the Arctic region of east Asia and Canada. The figure illustrates harmonic analysis of PFIv2: amplitude of the annual cycle or first harmonic.